Evaluasi Implementasi Program Ekstrakurikuler Pramuka di SDN Poris Pelawad 3 Kota Tangerang Banten - Nasa Nasa (CV. Syntax Corporation Indonesia, 2023)
This thesis aims to identify, analyze and evaluate the Scout extra-curricular program at SDN Poris Pelawad 3, Cipondoh District, Tangerang City, Banten. The method used is a qualitative method. Collecting data using observation, interviews and documentation. Interviews were conducted with school principals, teachers, school committees, parents and students. Evaluation analysis uses the CIPP (Context Input Process and Product) evaluation model. The research in this thesis is motivated by the lack of efficiency in the mandatory Scout extracurricular activities, and the role of teachers in motivating activities in the implementation of activities that take place every week is felt to be less than optimal and efficient. It can be seen that very few students are interested in joining scout exercises. The results obtained from this research are because students do not yet have values or norms of noble character. The input varies because students come from economic, social, cultural and educational backgrounds and the facilities and infrastructure are still inadequate. The process has been good, because all scout activities or work programs have been implemented properly, as evidenced by the several group achievements achieved by SD Negeri PorisPelawad 3 Tangerang. The product of students at SD Negeri Poris Pelawad 3 Tangerang got achievements but that was in groups, if as an individual, SD students still lack achievement. The real results that are felt by students, teachers and parents are the development of good character values of students after participating in extracurricular activities.